Assessing Quality of Sensitization Programs of State-Wide Youth Mental Health Promotion Program – An Indian Example - Upashana Medhi; Pradeep S. Banandur; B A Arvind; Gautham M. Sukumar; Rajeshwari; Sathya Velu; Vani Naik; Sonia Therat; Azad Devyani (Indian Journal of Community Medicine)
Background: Sensitization plays a pivotal role in raising awareness about critical youth issues and encouraging them to access support services, contributing to the success of programs like Yuva Spandana, a youth-centric mental health promotion initiative in Karnataka, India. For youth to access support within YSKs, the quality and effectiveness of sensitization programs (SPs) are crucial. A standard quality assessment through indicators for SPs is required to provide recommendations for improvement. To enlist quality indicators and assess the quality of SP conducted under Yuva Spandana (YS) program across Karnataka. Material and Methods: We performed secondary data analysis (utilizing data available within the computerized management information system over 5 years; 2017-2022) and direct/in-person observation of SPs (by the researcher and the core team of YS between June and July 2022 using a specifically developed checklist). Quality indicators were developed using a process of consensus building. Each attribute within the checklist was scored, and a composite mean score and mean percentage scores for quality were calculated. Results: Overall, 33257 SP reports and 31 in-person SPs were assessed. A total of 36 quality indicators (10 quality indicators based on SP reports and 26 based on in-person observation) were developed. The average quality score of report-based SPs was 10.93 (±2.59; range 1-20) and in-person assessment was 63.06 (±6.61; range 50-73). Conclusion: The study emphasizes the importance of addressing all youth issues, including sensitive topics like gender, sex, and sexuality, to ensure a holistic approach to youth mental health. Challenges faced during program execution and the distribution of Information, Education, and Communication (IEC) materials also contribute to program quality. This research offers valuable insights for improving the conduct of SPs, enhancing youth access to services, and guiding future community-based health promotion initiatives.